Kienbock`s disease that manifested in a badminton player: Case report - Karahan, A. Y.; Yesilyurt, S.; Kaydok, E.; Olcucu, B.; Bagcaci, S. (International Journal of Sports Science, 2013)
Badminton is considered to be a very safe sport, and is one of the most widely-played sports in the world. The reported frequency of badminton injuries are between one and four percent. The majority of the injuries are due to overuse, primarily in the lower limb. We report on a 23 year old professional badminton player who had painful and limited wrist movements, and was diagnosed with Kienbock`s disease (KD). KD is osteonecrosis of the lunate bone. The exact cause of KD is not known, though there are thought to be a number of factors predisposing a person to KD. Sports-related KD has been reported in tennis players, as well as in other sports. It is unusual in badminton players however, which is the basis of this report. The current case demonstrates the importance of raising awareness of these diseases as potential sports-related problems in the badminton players.